Military Protein Intake Related to Strength and Fat Mass Independent of Energy Intake. Issue 9 (7th July 2020) - Ross, Jeremy A; Thomas, D Travis; Winters, Joshua D; Royer, Scott D; Halagarda, Christopher J; Sheppard, Ryan; Abt, John; Heebner, Nicholas R
ABSTRACT: Introduction: Kinetic military units operate in austere training environments and deprivation not commonly experienced by competitive athletes. Nutritional strategies to protect against decrements in performance and potential injury risk may differ for these two groups. A cross sectional analysis was conducted to determine energy and macronutrient characteristics associated with performance metrics. Materials and Methods: 78 male subjects (age: 28.4 ± 6.0 years, height: 178.3 ± 6.7 cm, mass: 84.3 ± 9.4 kg, 8.5 ± 5.8 years of service) assigned to Marine Corps Forces Special Operations Command completed a 1-day performance assessment. Body mass, lean body mass, fat mass (FM), aerobic capacity (VO2max), lactate inflection point (LT), anaerobic power, anaerobic capacity, knee flexion strength, knee extension strength, peak knee flexion strength, and peak knee extension strength outcome values were recorded. Dietary intake was collected using automated self-administered 24-hour dietary recall (ASA24). Performance assessment scores were compared with macronutrient intake and controlled for energy intake using analysis of covariance. Results: Differences in knee flexion strength, knee extension strength, peak knee flexion strength, and peak knee extension strength were significant across low (LPRO), medium (MPRO), and high (HPRO) protein intake groups ( p  < 0.05) with LPRO performance metrics significantly lower than both MPRO and HPRO and MPRO significantly lower than HPRO. FM was significantly higher in LPRO than MPRO or HPRO ( p  < 0.05). Low carbohydrate intake (LCHO) was associated with greater body mass and FM compared with high (HCHO) ( p  < 0.05). There was no association between fat intake and any variable. Conclusions: Increases in protein intake may have beneficial performance effects independent of total energy intake, while moderate increases in carbohydrate intake may not be sufficient to enhance physical performance in a special operations population.